(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The use of interactive teaching methods in fine arts lessons is one of the most pressing problems today. The need to apply pedagogical technologies to interactive visual arts methods, such as brainstorming, clustering, conversation, debate, discussions, puzzles, role-playing games, arises from the study and analysis of the content of pedagogical technology and the essence of traditional education.